2013
DOI: 10.14203/jkti.v15i2.113
|View full text |Cite
|
Sign up to set email alerts
|

Karakteristik Bio-Oil Hasil Pirolisis Ampas Tebu

Abstract: Bagasse (Saccarum oficinarum L) is a waste of sugar mills that can be utilized for a variety of chemicals. The purposes of this study are to determine the percentage of compounds and physical properties of bio-oil, to determine the effect of variations of particle size and heating rate on the yields of bio-oil. Pyrolysis has been carried out in a reactor made of steel pipe type 5737 with dimension: diameter 7.62 em and a length of 3 7 cm.. The reactor was inserted into the furnace with a diameter of 15.24 em a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
3
0
2
Order By: Relevance
“…Dalam 100 ton tebu yang diproses dalam sebuah pabrik gula, akan menghasilkan sekitar 30 ton ampas tebu basah [11]. Sejauh ini, hanya 30-50% ampas tebu yang sudah dimanfaatkan antara lain; sebagai bahan baku produksi bioetanol, dibakar untuk menghasilkan uap pada pembangkit listrik, bahan baku kertas, bahan baku industri kanvas rem, industri jamur, dan lain-lain, sedangkan sisa residu lainnya belum termanfaatkan secara optimal [11], [19].…”
Section: Gambar 1 Jumlah Produksi Gula DI Indonesiaunclassified
See 1 more Smart Citation
“…Dalam 100 ton tebu yang diproses dalam sebuah pabrik gula, akan menghasilkan sekitar 30 ton ampas tebu basah [11]. Sejauh ini, hanya 30-50% ampas tebu yang sudah dimanfaatkan antara lain; sebagai bahan baku produksi bioetanol, dibakar untuk menghasilkan uap pada pembangkit listrik, bahan baku kertas, bahan baku industri kanvas rem, industri jamur, dan lain-lain, sedangkan sisa residu lainnya belum termanfaatkan secara optimal [11], [19].…”
Section: Gambar 1 Jumlah Produksi Gula DI Indonesiaunclassified
“…Ref. [19] juga melakukan penelitian dengan variasi diameter partikel yaitu (-20+25), (-25+30), (-30+35), (-35+40) dan -40 mesh serta kecepatan laju pemanasan yaitu 100, 105, 110 dan 120 volt. Didapatkan yields tertinggi pada diameter partikel terkecil yaitu (-20+25) mesh sebesar 40,32 %.…”
Section: Hasil Dan Pembahasan 31 Konversi Ampas Tebu Menjadi Bio-oilunclassified
“…The second model used is a modification of the reaction mechanism proposed by Koufupanos [32] which is also used by Erawati [35]. The reaction mechanism of the second model can be seen in Fig.…”
Section: Model IImentioning
confidence: 99%
“…Special Task Force for Upstream Oil and Gas Business Activities of Republic Indonesia (SKK Migas) (ESDM, 2016) showed that the petroleum reserves are estimated to decrease from 4.3 billion barrels in early 2004 to 3.7 billion in 2014. Indonesia's alternative fuel consumption in 2011-2015 is 4.52 million kilo liters of biodiesel, 2.78 million kilo liters of bioethanol, 1.8 million kilo liters of bio-oil, and 9.84 million kilo liters of biofuels (Erawati et al, 2013). Depletion of the fossil fuels reserves made the development of alternative fuels such as bio-oil urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Bio-oil is an inorganic liquid which produced by pyrolysis process (Erawati et al, 2013). Bio-oil can be produced from biomass.…”
Section: Introductionmentioning
confidence: 99%